'I feel like I have a voice': promoting mental health among Australian high school students through public speaking. (2nd September 2021) - Isobel, Sophie; Pretty, Danielle; Meehan, Felicity; Smith, Nicole
ABSTRACT: Objective: This study explored the experience of student and teacher participants in a mental health public speaking challenge, including their self-reported knowledge of mental health, mental health literacy and stigma. Method: A qualitative inquiry was undertaken. Questionnaires were distributed to student participants and audience members. Sixty-four completed questionnaires were analysed using content analysis. Five semi-structured interviews were undertaken with teachers. Interview transcripts were analysed thematically. Results: Students described the effects of the challenge on stigma and benefits for them personally and the wider school, including their confidence in supporting peers. Teacher interviews highlighted the commitment required, the preparation needed, the benefits for the individuals and schools, and the process and practicalities of the challenge. Discussion: The MHPSC provides a forum for embedding mental health literacy into education for high school students. While the MHPSC requires support to ensure its delivery, for students it fosters knowledge, awareness and peer-support related to mental health. The findings can inform preventative and early intervention activities across health and education domains.